Designing and enacting instruction that enhances language for mathematics learning - a review of the state of development and research - Erath, K; Ingram, JJ; Moschkovich, J; Prediger, S (Springer Nature, 2021)
After four decades of research and development on language in mathematics classrooms, there is consensus that enhancing language is crucial for promoting students’ mathematics learning. After briefly sketching the theoretical contexts for work on this topic, the article presents six design principles for instruction that enhance language for mathematics learning. It then reviews the research that provides an empirical foundation for these principles, (a) concerning the design of learning environments to enhance language for mathematics learning and (b) on teaching practices (including teacher moves and classroom norms) involved in the enactment of those designed learning environments. Without claiming completeness, this review of the state of development and research shows that some aspects of design and instruction that enhance language for mathematics learning have been well researched, whereas research gaps for other aspects persist.